2001
DOI: 10.1088/0963-0252/10/3/318
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic studies of species concentrations in a capacitively coupled RF plasma containing CH4-H2-Ar

Abstract: Three plasma diagnostic methods, tunable infrared diode laser absorption spectroscopy, optical emission spectroscopy and microwave interferometry have been used to monitor concentrations of transient and stable molecules, CH 3 , CH 4 , C 2 H 2 , C 2 H 6 , and of electrons in capacitively coupled CH 4 -H 2 -Ar radiofrequency (RF) plasmas (f RF = 13.56 MHz, p = 100 Pa, φ total = 66 sccm) for various discharge power values (P = 10-100 W) and gas mixtures. The degree of dissociation of the methane precursor varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…It has been suggested that hydrocarbon radicals, such as CH x (x = 1, 2, 3), are very important species. [41][42][43][44] As reported previously, the formation energy of single vacancies (SV) in graphene is very large (about 7.5 eV). [45,46] Thus, it is very probable that interaction with reactive species can effectively lead to the healing of SV to restore a perfect graphene structure.…”
Section: Introductionmentioning
confidence: 54%
“…It has been suggested that hydrocarbon radicals, such as CH x (x = 1, 2, 3), are very important species. [41][42][43][44] As reported previously, the formation energy of single vacancies (SV) in graphene is very large (about 7.5 eV). [45,46] Thus, it is very probable that interaction with reactive species can effectively lead to the healing of SV to restore a perfect graphene structure.…”
Section: Introductionmentioning
confidence: 54%
“…The most straightforward measurement of these parameters with Langmuir probe (LP) is unfortunately not possible due to the formation of insulating layer on the probe tip and other methods has to be used. Microwave interferometry has been used instead to measure electron densities in CH 4 and C 2 H 2 containing plasmas [57,84,85]. Alternatively, a plasma absorption probe [86,87] can be used and it has been applied to measure electron density in Ar/C 2 H 2 plasma containing dust particles [88].…”
Section: Experimental Techniques For Study Of Pcrsmentioning
confidence: 99%
“…The IRMA system has been applied successfully in several studies of molecular phenomena in plasmas, e.g. [38,62,68,70,94,128,129].…”
Section: The Irma Systemmentioning
confidence: 99%